JANGKA WAKTU PUTUSAN KASASI NOMOR.006/K/PDT.SUS-HKI/2021 TENTANG SENGKETA MEREK ANTARA PT. SUPRA TERATAI METAL MELAWAN PT. WIHARTA PRAMETAL : - Yustika Nainggolan; Asep Iwan Iriawan (Reformasi Hukum Trisakti, 2023)
Trademarks are used to identify or recognize the origin of goods and services. Several factors can trigger trademark disputes. This research discussing how the judges consider the legal aspects when examining and deciding trademark cases between PT Supra Teratai Metal and PT Wiharta Prametal, and what the legal consequences are if the cassation application in the trademark dispute exceeds the cassation time frame based on the applicable law. This research type is normative legal research, with qualitative data processing, a descriptive research nature, and deductive conclusions. The results of this research show that during the cassation application review process, the panel of judges found that the Defendant's trademark had not been officially registered. Therefore, from a legal perspective, the cassation applicant is the official holder of the registered trademarks, the sentence you provided appears to be in Indonesian and discusses a dispute over a trademark between PT Supra Teratai Metal and PT Wiharta Prametal. It mentions that the judge in examining the trademark dispute may have violated Article 2 paragraph (4) of Law No. 48 of 2009. The violation of this law could serve as a basis for the Respondent in Cassation to file a legal effort for a review.